Study on the quarterly sector of economy aiming the information society development - Botelho, Tânia Maria (1990)
Presents different approaches and concepts of the Quartenary space. Stresses the important role of information to the development of nations in the last decades and its share in the knowledge intensive industries sector. Reports on other studies worked out on social and economic changes in society, emphasizing occupational and social structures. Analyses perspectives and relationships between Northern and Southern countries, with particular reference to technological, economic, social, polítical and cultural aspects. The related issues of interdependence among developing countries and the high developed ones are treated from a transystemic approach. Evocates the present scenario in Brasil as a challenge to information professionals in the process of change needed in the social and economic leverage.